Saturday, March 3, 2012

Fibonacci from golden ratio using power series



While reading about Fibonacci series, I came across the formula which gives the Fibonacci number using golden ratios. I was curious about how did such an equation was derived and how could it give the answer so correctly. This problem introduced me to the world of generating function. I will start with a few definitions.

A formal power series is an expression of the form
a+ a1x + a2x+ …
where a is a coefficient.

A generating function is a formal power series whose coefficients give the sequence { a0, a1, a2, … }. A general idea is as follows. In counting problems we are often interested in counting the number of objects of size , which we represent represent as a. By varying n, we get different values of an. In this way, we get a sequence of real numbers a0, a1, a2, … 
from which we can define a power series
G(x) = a+ a1x + a2x+ …

The above G(x) is the generating function for the sequence a0, a1, a2, … 

Let us find an explicit formula for finding nth element of the fibonacci series
First, we will define some useful results.
1 and -ϕ2 be roots of the equation (x+ x – 1)
ϕ= (1 + √5)/2 and ϕ2 = (1  √5)/2
Therefore, ϕ ϕ√5  .......(1)
and ϕ1.ϕ1 .........(2)
We know that for a fibonacci number Fn,
Fn = Fn-1 + Fn-2
or Fn  Fn-1 – Fn-2  = 0
F0 = 0, F1 = 1.
Let the generating function for Fn be  
F(x) = F0 + F1x + F2x2 + F3x+ ...
Now, multiplying F(x) with 1, -x and -xand, adding them
                   F(x) = F1x + F2x+ F3x+ ...
                –xF(x) =       – F1x2 – F2x–  F3x4 ...
               –x2F(x) =                  – F1x3– F2x– F3x5 ...
_____________________________________________
(1 – x  – x2).F(x) = x    + 0       + 0     + 0 ....
or F(x) = –x/(x+ x – 1)

Using partial fractions, we decompose 
F(x) = A/(x + ϕ1) + B/(x + ϕ2)
or –x/(x+ x – 1) = A/(x + ϕ1) + B/(x + ϕ2)
or -x = A(x + ϕ2) + B(x + ϕ1)
Putting x = -ϕ2, we have ϕ= B(-ϕ2 + ϕ1),
or B = ϕ2/√5
Putting x = -ϕ1, we have ϕ1 = A(-ϕ1 + ϕ2),
or A= -ϕ1/√5


Therefore,
F(x) = (-ϕ1/√5)/(x + ϕ1) + (ϕ2/√5)/(x + ϕ2)
       = -(1/√5)/(1 + x/ϕ1) + (1/√5)/(1 + x/ϕ2)
       = -(1/√5)/(1 - xϕ2) + (1/√5)/(1 - xϕ1)             [From 2]
       = -(1/√5)Σ(xϕ2)+ (1/√5)Σ(xϕ1)n                 [From the equation for summation of G.P series] 
       = (1/√5)Σ(ϕ1n - ϕ2n)xn


Therefore, the coefficient of xwill give Fn


Finally, we have
Fn = (1/√5)(ϕ1ϕ2n)

To learn more about generating functions check this out.

No comments:

Post a Comment